Thailand : Detailed Assessment Report on Anti-Money Laundering and Combating the Financing of Terrorism. (IMF Staff Country Reports; Country Report, 2007)
This Detailed Assessment Report focuses on Anti-Money Laundering and Combating the Financing of Terrorism (AML/CFT) for Thailand. The report discusses that Thailand has a legal framework in the Anti-Money Laundering Act 1999 (AMLA) around which the core elements of its AML/CFT regime are established. The AMLA criminalizes money laundering by reference to eight predicate offenses and establishes the Anti-Money Laundering Office (AMLO) as Thailand's financial intelligence unit. It imposes some customer due diligence obligations on a wide range of financial institutions (FIs) and requires these FIs to report transactions to the AMLO.